FUZZY ANALYTIC HIERARCHY PROCESS BERBASIS MORFOMETRI UNTUK PRIORITAS PENANGANAN EROSI DI SUB DAERAH ALIRAN SUNGAI OYO (Fuzzy analytic hierarchy process based on watershed morphometry for erosion priority mapping in Oyo Sub Watershed) - Alfiatun Nur Khasanah; Arina Miardini (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2020)
ABSTRACTErosion is an indication of watershed degradation. In a watershed management, it is necessary to prioritize the handling that takes into account the characteristics of the watershed, one of which is morphometric character. This study aims to determine the priority location of erosion management in Oyo Watershed based on morphometric data using Fuzzy AHP modeling. Morphometric parameters that affect erosion are Rbm (bifurcation ratio), Rc (circulatory ratio), Dd (drainage density), T (texture), Su (Gradient) and Rn (Rugness Number). The highest value of the output shows the priority location that should be controlled. The high priority levels are found in 21 sub-watersheds with an area of 3,82 ha, medium levels are in 35 sub-watersheds with an area of 17,780.21 ha, low levels are in 106 sub-sub Watersheds with an area of 48,974.46 ha. The priority order for erosion management at the sub-watershed level is very important to prepare a watershed management plan in order to control soil erosion that is appropriate to protect the soil from further erosion.Keywords: fuzzy-AHP; morphometry; priority; erosion; Oyo Sub-watershed   ABSTRAKErosi merupakan salah satu indikasi kerusakan DAS. Dalam pengelolaan DAS perlu dilakukan urutan prioritas penanganan dengan memperhatikan karakteristik DAS, salah satunya yaitu karakter morfometri. Penelitian ini bertujuan untuk mengetahui lokasi prioritas penanganan erosi di Sub DAS Oyo berdasarkan data morfometri dengan menggunakan pemodelan Fuzzy AHP. Parameter morfometrik yang mempengaruhi erosi adalah Rbm (bifurcation ratio), Rc (circulatory ratio), Dd (drainage density), T (texture), Su (gradient), dan Rn (rugness number). Nilai tertinggi dari hasil analisis menunjukkan lokasi prioritas yang harus didahulukan penanganan erosinya. Tingkat prioritas tinggi terdapat pada 21 sub-sub DAS dengan luas 3.82 ha, tingkat sedang pada 35 sub-sub DAS dengan luas 17.780,21 ha, tingkat rendah pada 106 sub-sub DAS dengan luas 48.974,46 ha. Urutan prioritas penanganan erosi pada tingkat sub DAS sangat penting untuk menyusun rencana pengelolaan DAS dalam rangka pengendalian erosi tanah yang sesuai sebagai upaya perlindungan tanah dari erosi lebih lanjut.Kata kunci: fuzzy-AHP; morfometri; prioritas; erosi; Sub DAS Oyo